Competence of Military Justice in Criminal Disputes of Servicemen - Maswandi, Maswandi (International Asia Of Law and Money Laundering (IAML), 2025)
This study comprehensively analyzes the competence of the military judiciary in examining, prosecuting, and deciding criminal cases involving active soldiers of the Indonesian National Army (TNI), using the Appeal decision Number 88-K/PMT.I/BDG/AL/IX / 2025 as the main case study. In the case, the defendant, who is a navy soldier, was charged with committing a military crime in the form of disobedience to official orders, actions that have the potential to disrupt discipline, command hierarchy, and unit operational order. The verdict of the first instance was handed down by the Bandung high military court I, which was then re-examined in the appeal level after legal remedies were filed by the relevant parties.The appellate panel of judges reviewed the case by considering a number of important juridical aspects, including the absolute competence of Military Justice based on the provisions of Law No. 31 of 1997 on Military Justice, the fulfillment of criminal elements as stipulated in the Criminal Code, and the imposition of crimes that reflect the principle of proportionality and Justice. The appeal ruling also confirmed that the jurisdiction of Military Justice is determined not only by the status of the subject of Law (active soldier), but also by the direct interrelation of criminal acts and military service duties.Through normative legal research methods that combine legislative, doctrinal, and analysis approaches to court decisions, this study found that military justice has full and indisputable competence in dealing with these types of cases, especially when the actions of the accused are directly related to the performance of official duties and affect discipline and command structure. The panel of judges at the appeal level consistently confirms the fulfillment of elements of military offenses, both subjective and objective elements, based on the facts of the trial and valid evidence according to the law of military procedure.Thus, this study concludes that the appeal verdict is a real representation of the consistency of the application of the law in military criminal justice. This ruling not only strengthens the absolute authority of the military judiciary in prosecuting soldiers who commit violations within the scope of service, but also makes an important contribution to legal certainty, official order, and the integrity of the military justice system in Indonesia. In addition, the decision emphasized the function of Military Justice as an instrument for fostering discipline, maintaining the professionalism of soldiers, and ensuring the implementation of military life in accordance with the principles of hierarchy and command.